Kaposi Sarcoma of the Eye in an HIV Patient Well-responded to HAART - Erni J Nelwan; Laurentius A Pramono; Anna M Lubis; Zubairi Djoerban (Acta Medica Indonesiana)
Kaposi sarcoma defined as a multifocal lesion in mucocutaneous sites which has low-grade malignant potential. Kaposi sarcoma also commonly found in visceral organs. This malignancy is very popular among elderly men before the epidemic of HIV/AIDS in the decade of 1980-1990 Kaposi sarcoma known to be associated with immunodeficiency state as in HIV/AIDS patients. Nowdays, incidence of Kaposi sarcoma has decreased in developed countries in the era of Highly Active Antiretroviral Therapy (HAART) but still a big problem in resource-limited areas such as Sub- Saharan Africa.